2010
DOI: 10.1007/s10763-010-9199-2
|View full text |Cite
|
Sign up to set email alerts
|

Equity in Mathematics and Science Outcomes: Characteristics Associated With High and Low Achievement on Pisa 2006 in Ireland

Abstract: ABSTRACT. Equity in education is a key concern internationally; however, it is rare that this issue is examined separately for low-and high-achieving students and concurrently across different subject domains. This study examines student and school background characteristics associated with low and high achievement in mathematics and science on the Programme for International Student Assessment. Based on the results of a multilevel multinomial model of achievement for each domain, findings indicate that a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 7 publications
0
17
0
3
Order By: Relevance
“…Through the conceptual tools of Bourdieu, the paper explores the complexity of how two similarly positioned individuals can start to diverse in their career aspirations and identifications with science. The findings can shed light into studies which suggests that the underrepresentation of girls and minority ethnic groups in science (at post-compulsory level) to be the result of lower science attainments (Elias et al, 2006;Gilleece, Cosgrove, & Sofroniou, 2010;Thomson, 2008), since both girls in this paper are considered 'high' achievers. In this paper, the case of Samantha explicates how 'working class' British Asian schoolgirls can aspire to study 'triple science' without interest, while the case of Fay examines how her desires to be 'famous' can potentially interfere with her science education and, in particular, her academic attainment.…”
Section: Based December 2010 Feedbacks -Key Changes Highlighted In Yementioning
confidence: 59%
“…Through the conceptual tools of Bourdieu, the paper explores the complexity of how two similarly positioned individuals can start to diverse in their career aspirations and identifications with science. The findings can shed light into studies which suggests that the underrepresentation of girls and minority ethnic groups in science (at post-compulsory level) to be the result of lower science attainments (Elias et al, 2006;Gilleece, Cosgrove, & Sofroniou, 2010;Thomson, 2008), since both girls in this paper are considered 'high' achievers. In this paper, the case of Samantha explicates how 'working class' British Asian schoolgirls can aspire to study 'triple science' without interest, while the case of Fay examines how her desires to be 'famous' can potentially interfere with her science education and, in particular, her academic attainment.…”
Section: Based December 2010 Feedbacks -Key Changes Highlighted In Yementioning
confidence: 59%
“…Este é um tema referenciado noutros estudos internacionais (CORDERO FERRERA; CRESPO CEBADA; SANTÍN GONZÁLEZ, 2010;FERRER;VALIENTE;CASTEL, 2010;GILLEECE;COSGROVE;SOFRONIOU, 2010).…”
Section: (V) Uso Das Tecnologias Da Informação E Comunicação (Tic)unclassified
“…Similar results were found in PISA 2000 mathematics literacy with male students outperforming female students by 11 points across 43 participating countries (OECD 2003). However, some studies showed that female students outperformed male students (e.g., Gilleece et al 2010; Tsai and Walberg 1983). In this study, at the student level, female and male students were recoded as 0 and 1, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%